2017
DOI: 10.1038/nplants.2016.204
|View full text |Cite
|
Sign up to set email alerts
|

ABA-unresponsive SnRK2 protein kinases regulate mRNA decay under osmotic stress in plants

Abstract: Rapid changes in messenger RNA population are vital for plants to properly exert multiple adaptive responses under continuously changing stress conditions. Transcriptional activation mediated by the 'abscisic acid (ABA)-activated SnRK2 protein kinases-ABA-responsive element (ABRE)-binding proteins/ABRE-binding factors (AREB/ABFs)' signalling module is a crucial step in the expression of stress-inducible genes under osmotic stress conditions in Arabidopsis. In addition to transcriptional control, proper transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
130
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(145 citation statements)
references
References 27 publications
14
130
0
1
Order By: Relevance
“…Osmotic stress triggers SnRK2 localization in PBs, where they appear to phosphorylate and regulate VCS function (Soma et al, 2017). Mutations that prevent DCP1 or VCS phosphorylation render Arabidopsis plants susceptible to osmotic stress (Xu and Chua, 2012;Soma et al, 2017). These observations firmly suggest that transcriptome adjustments mediated by mRNA decapping are relevant to stress resilience.…”
Section: Decappingmentioning
confidence: 98%
See 1 more Smart Citation
“…Osmotic stress triggers SnRK2 localization in PBs, where they appear to phosphorylate and regulate VCS function (Soma et al, 2017). Mutations that prevent DCP1 or VCS phosphorylation render Arabidopsis plants susceptible to osmotic stress (Xu and Chua, 2012;Soma et al, 2017). These observations firmly suggest that transcriptome adjustments mediated by mRNA decapping are relevant to stress resilience.…”
Section: Decappingmentioning
confidence: 98%
“…By contrast, VCS is phosphorylated by the abscisic acid (ABA)-unresponsive osmotic stress-activated subclass I of SUCROSE NONFERMENTING1-RELATED PROTEIN KINASE2s (SnRK2s). Osmotic stress triggers SnRK2 localization in PBs, where they appear to phosphorylate and regulate VCS function (Soma et al, 2017). Mutations that prevent DCP1 or VCS phosphorylation render Arabidopsis plants susceptible to osmotic stress (Xu and Chua, 2012;Soma et al, 2017).…”
Section: Decappingmentioning
confidence: 99%
“…The accumulation of antisense RNA was affected by the amount of the substrate that is generated by changes of RNA degradation metabolism under drought stress. Recently, it has been reported that mRNA decay pathway plays an important role in plant stress and hormone responses (Abler and Green, 1996, Kuhn and Schroeder, 2003, Riehs-Kearnan et al, 2012Soma et al, 2017). DCP1 and VARICOSE were phosphorylated by MPK6 and SnRK2, respectively, when plants were subjected to drought stress Soma et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that mRNA decay pathway plays an important role in plant stress and hormone responses (Abler and Green, 1996, Kuhn and Schroeder, 2003, Riehs-Kearnan et al, 2012Soma et al, 2017). DCP1 and VARICOSE were phosphorylated by MPK6 and SnRK2, respectively, when plants were subjected to drought stress Soma et al, 2017). Phosphorylated DCP1 preferentially bound to DCP5 and promoted the decapping of direct mRNA targets, whereas dcp5 mutants were hypersensitive to osmotic stress .…”
Section: Discussionmentioning
confidence: 99%
“…The Arabidopsis triple knockout mutant snrk2.2/snrk2.3/snrk2.6 is extremely insensitive to ABA (much more than the single or double knockout mutants), exhibits severely impaired seed development and dormancy, and is oversensitive to water scarcity due to disruption of stomatal closure and down-regulation of ABA-and water stress-induced genes (Fujii and Zhu, 2009; Fujita et al, 2009; Nakashima et al, 2009). SnRK2s, which are either not or only weakly activated in response to ABA, are also involved in regulation of plant responses to abiotic stresses (Umezawa et al, 2004; Mizoguchi et al, 2010; Fujii et al, 2011; McLoughlin et al, 2012; Kulik et al, 2012; Soma et al, 2017).…”
Section: Introductionmentioning
confidence: 99%